Ein Neues Buch zu den Regna Minora - Schottky, Martin (Anabasis. Studia Classica et Orientalia, 2019)
[Review article of: Michał Marciak, Sophene, Gordyene, and Adiabene. Three Regna Minora of Northern Mesopotamia between East and West (Impact of Empire, Volume 26), Leiden – Boston: Brill, 2017, XVI and 581 pp., 78 figures and maps, ISSN 1572-0500, ISBN 978-90-04-35070-0 (hardback), ISBN 978-90-04-35072-4 (e-book)]